An Approach to María de los Reyes Fuentes and her Poetic Cycles - Aguilar González, Juan (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This work proposes an approach to the figure of María de los Reyes Fuentes and her poetry, as well as an analysis of the poetic cycles in which her work is divided. Although we have decided here for a division into two parts, we will also trace a tour through the changes that this division has undergone as a result of subsequent studies. For this purpose, two works have been taken as reference for the first stage and three for the second, following a criterion of relevance and representativeness. The study carried out shows that, although love poetry almost disappears in the second stage, it is not possible to establish a clear division between the two cycles since there is a thematic continuity. This research is part of the project “Hidden Andalusian women”, which aims to recover the names, lives and works of the women writers of the Silver Age.